Perceptivna primerjava kot temelj filozofije umetnosti - Harry Lehmann (Phainomena, 2018)
Perceptual Comparison as the Foundation for Art Philosophy - “Aesthetic is …?” We can finish this sentence in two different ways. “Aesthetic is …” could be understood as the science of perception, and “Aesthetic is …” could be understood as philosophy of art. What the author tries to do in the article is to present his theory which works on closing the gap between these two traditions of aesthetics. He developed this theory in his book Gehaltsästhetik. Eine Kunstphilosophie (Contentsaesthetics. A Philosophy of Art), which was published in January 2016. In the table of contents, you can see that the first two chapters are developed within the tradition of aesthetic as a science of perception (here the author introduces a new theory of aesthetic experience and a theory of eigenvalues of perception), and the following two chapters belong to the tradition of art-philosophy. Here the author introduces a theory of reflexive values and by the help of this theory, he is able to reconstruct major caesuras in the history of the Western art.